2021
DOI: 10.1016/j.jvscit.2021.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Acute limb ischemia and aortic mural thrombosis as primary manifestations of severe acute respiratory syndrome coronavirus 2

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Several studies reported that critically ill patients with COVID-19 were at risk of having various complications, such as ARDS, AKI, acute liver failure, acute cardiac injury, septic shock, or secondary infections [ 11 , 31 , 32 , 33 ]. In the current study, the most common complications were ARDS and septic shock, followed by AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that critically ill patients with COVID-19 were at risk of having various complications, such as ARDS, AKI, acute liver failure, acute cardiac injury, septic shock, or secondary infections [ 11 , 31 , 32 , 33 ]. In the current study, the most common complications were ARDS and septic shock, followed by AKI.…”
Section: Discussionmentioning
confidence: 99%